A Contribution To The Cross - Cultural Replicability Of The Five-Factor Personality Model - Marušić, Iris (Array, 1996)
Over the recent years numerous studies have contributed to the evidence of cross-cultural validity of the five-factor model as the most adequate paradigm for description of the personality domain. The aim of this study was to validate Croatian translation of the most widely used five-factor questionnaire, NEO PI-R (Costa & McCrae ; 1992b). The research was carried out on two samples of subjects. The first sample consisted of 466 high school graduates, 233 males and 233 females, whose mean age was 18. The second sample consisted of 256 adults, 123 males and 133 females, whose mean age was 46 years. Alpha reliabilities in both samples were very high for all five scales, and are in the range of values obtained on the normative American sample. Correlations among the scales are also comparable to those reported by authors of the questionnaire. Furthermore, factor analysis of the facets in both samples provided close replications of the original factor structure. Results of our validation study clearly show that NEO-PI R is a valid instrument for the assessment of five broad personality dimensions in Croatian population, and thus are still another contribution to the empirical evidence on the universality of the five-factor model.